நாலாயிர திவ்ய பிரபந்தத்தில் திருஅவதாரக் கொள்கைகள் (விபவ நிலை) / The Divine Avatar Doctrines in Nalayira Dhivya Prabantham (Vibhava State) - ம. வெங்கடலட்சுமி / M. Venkatalakshmi; முனைவர் ச. குருஞானாம்பிகா / Dr. S. Gurugnanambiga (Pandian Tamil Journal of Temple Studies, 2023)
In the Tamil language, religion is understood to be related to people's life and morals. The word ‘religion’ has many meanings such as ethics and principles. Religion is the name given to the philosophy of ripening human souls as fertile fields of sweet love. Since the beginning of the world, various religions have appeared and developed to improve people's lives. Literature shows that religions are closely related to people's lives. The crutch of religion is that a human being should set his life in order, and for that, he should adhere to certain morals or values and conduct himself accordingly. It is considered important to swim across the ocean of birth and surrender to God. If one wants to get the grace of God in the present Kali Yuga, one has to yearn in heart and worship God with true love. It is pointed out in Vaishnavism that one should praise the name of Lord Vishnu and appreciates the mercy that the Lord has towards living beings, and those who follow Him will attain an easy way to achieve ‘prabhati’. These are the doctrines of Vaishnavism. Therefore, the Vaishnava literature is to explain that Thirumal, the Vaishnava God, has taught virtue to the people of the world through the incarnations he has taken.